THE ASH'ARI ROOTING FOR THE ATTRIBUTES OF DIVINE MEANINGS ... IMAM AL-JUWAYNI AS A MODEL, IN THE LIGHT OF HIS BOOK WITH SHINING OF EVIDENCE IN THE RULES AND BELIEFS OF THE SUNNIS - MAJEED , FIRAS (Islamic Sciences Journal, 2023)
Research summary that :: 1- Imam Al-Juwaini is one of the imams of the Sunnis and the community. Ash'ari's doctrine Shafi’i school of thought studied many students in his time and was famous for his request for knowledge and the abundance of his works in most of the legal sciences, especially the science of speech. 2- The topics of the book (Shining of Evidence in the Rules and Doctrines of the People of the Sunnah) came sequential and continuous, as the talk began about the world and its occurrence to reach the existence and introduction of Allah Almighty, then he moved on to talk about Allah Almighty and his attributes. 3- Ash'ari went on to say that the moral or mental attributes of Allah are confined to seven attributes, and they differed on the characteristic of survival and have been proven by the evidence of reason (which is that he is alive, knowledgeable, capable, desirous, hearing, speaking, remaining). 4- In a very clear way, the Al-Juwayni approach appears, as Abu Al-Ma’ali demonstrated these qualities mentioned in the book and it is true of the Sunnah, even that which was fixed in the news of the ones without mentioning what was often mingled around him, which is known as the mental opponent. 5- Al-Juwayni chose that survival is due to the same continuous existence without more meaning, and the reason for this is that the mind sees that if this path does not follow, we should describe the eternal qualities as remaining, then we prove to it survival and the context of this saying is carried out to the meaning in the meaning 6- The teams of the Kharijites, the Mu'tazilites, the Jahmiyyah and the Al-Muruja deny all the characteristics of Allah Almighty.